Abstract graphs, abstract paths, grounded paths for Freebase and NELL - Nastase, Vivi; Kotnis, Bhushan (Universität, 2019)
We describe a method for representing knowledge graphs that capture an intensional representation of the original extensional information. This rep...
Production date 2019
Gesehen am 16.07.2019
Keywords: Forschungsdaten; Datenbank